The effectiveness of Instagram as a marketing tool for Naelofar Hijab / Nornatasya Farina Jasman, Mohamed Razeef Abdul Razak and Azahar Harun - Jasman, Nornatasya Farina; Abdul Razak, Mohamed Razeef; Harun, Azahar (Faculty of Art and Design, 2022)
According to a survey conducted by the Malaysia eCommerce Industry, the hijab industry in Malaysia is a very profitable business that is expected to generate US $5.9 billion by 2024, according to the survey. Because of this, the study investigates the effective marketing strategy of the Naelofar Hijab brand as depicted on the Instagram platform to engage with the target audience. As a successful brand, this is even more important than other aspects of the Instagram marketing strategy. The AIDA model was used to analyze the ten most successful Naelofar Hijab Brand campaigns promoted on the Instagram social media platform. Naelofar Hijab was the most successful Brand that used Instagram as a marketing strategy tool to promote their products and grow their customer base and brand awareness. According to preliminary findings, Naelofar Hijab's marketing communication research is primarily defined as a strategy on Instagram focused on viral marketing techniques to draw the audience's attention to the Brand itself rather than the product itself. Other competitors in the fashion hijab category are also taking advantage of the Instagram platform to market their products. Despite this, the marketing techniques employed by the Naelofar Hijab brand are more distinctive in fostering loyalty, trust, inspiration, and motivation in the Brand, as demonstrated by the Brand's founder, Noor Neelofa on her Instagram account. As a result of the AIDA model approach, the findings of this study will benefit the community by increasing knowledge and strengthening entrepreneurial skills in them, allowing them to develop a successful marketing strategy.